Differences in the delivery of medications for opioid use disorder during hospitalization by racial categories: A retrospective cohort analysis. Issue 1 (1st December 2022) - Priest, Kelsey C.; King, Caroline A.; Englander, Honora; Lovejoy, Travis I.; McCarty, Dennis
Abstract: Background : As the drug-related overdose crisis and COVID-19 pandemic continue, communities need increased access to medications for opioid use disorder (MOUD) (i.e., buprenorphine and methadone). Disparities in the type of MOUD prescribed or administered by racial and ethnic categories are well described in the outpatient clinical environment. It is unknown, however, if these disparities persist when MOUD is provided in acute care hospitals. Methods : This study assessed differences in the delivery of buprenorphine versus methadone during acute medical or surgical hospitalizations for veterans with opioid use disorder (OUD) by racial categories (Black Non-Hispanic or Latino vs. White Non-Hispanic or Latino). Data were obtained retrospectively from the Veterans Health Administration (VHA) for federal fiscal year 2017. We built logistic regression models, adjusted for individual and hospital-related covariates, and calculated the predicted probabilities of MOUD delivery by racial categories. Results : The study cohort ( n  = 1, 313 unique patients; N  = 107 VHA hospitals) had a mean age of 57 (range 23 to 87 years), was predominantly male (96%), and composed entirely of Black (29%) or White (71%) patients. White patients were 11% more likely than Black patients to receive buprenorphine than methadone during hospitalization ( p  = 0.010; 95% CI: 2.7%, 20.0%). Among patients on MOUD prior to hospitalization, White patients were 21% more likely than Black patients to receive buprenorphine ( p  = 0.000; 95% CI: 9.8%, 31.5%). Among patients newly initiated on MOUD during hospitalization, there were no differences by racial categories. Conclusion : We observed disparities in the delivery of buprenorphine versus methadone during hospitalization by racial categories. The observed differences in hospital-based MOUD delivery may be influenced by MOUD received prior to hospitalization within the racialized outpatient addiction treatment system. The VHA and health systems more broadly must address all aspects of racism that contribute to inequitable MOUD access throughout all clinical contexts.